Measuring wildland fire fighter performance with wearable technology. (March 2017) - Parker, Richard; Vitalis, Antonios; Walker, Robyn; Riley, David; Pearce, H. Grant
Abstract: Wildland (rural) fire fighting is a physically demanding and hazardous occupation. An observational study was conducted to explore the use of new technologies for the field study of fire fighters at wildfires and to understand the work pressures of wildland fire fighting. The research was carried out with two fire fighters at real fires wearing microphones, miniature video cameras, heart rate monitors and GPS units to record their actions and location at wildfire events. The fire fighters were exposed to high physiological workloads (heart rates of up to 180 beats per minute) and walked considerable distances at the fires. Results from this study have been used in presentations to fire fighters and non-operational fire personnel to understand the pressures fire fighters are under and how others complete the fire fighting tasks. Highlights: A wearable ensemble of sensors is presented. Physiological and productivity data of wildland fire fighters is collected. Data is integrated to give insights of work at real wildland fires.